The gift relationship : from human blood to social policy / Richard M. Titmuss. - Titmuss, Richard Morris, 1907-1973 (Policy Press, 2018)
In this reissued classic, Richard Titmuss compares blood donation in the US and UK, contrasting the British system of reliance on voluntary donors to the American one in which the blood supply is in the hands of for-profit enterprises, concluding that a system based on altruism is safer and more economically efficient.